(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
There have always been two purposes for literature. There are many who appreciate it just asart, while others see in it a reflection of modern culture. These two ideas are the bedrock upon which allgreat fiction is constructed. Classicists, neoclassicists, romanticists, Marxists, modernists,postmodernists, deconstructivity, post colonialists, feminists, and so on have all weighed in on variousliterary value debates throughout history. However, environmental concern as shown in literature wasmostly ignored for a long period in literary studies. Eccritics do more than merely read a work theyapply a critical eye to it, looking for evidence of nature and literature’s mutual influence in order toemphasize these themes. In this way, they connect the world of literature to the real world. There iswidespread agreement that literature serves as a mirror for culture. Indeed, literature is a reflection ofculture, both positively and negatively. Literature has a redemptive purpose by reflecting societal flawsin an effort to help people see where they’ve gone wrong and make right. In addition, it displays thequalities and ideals of the society for individuals to aspire to. Literature, being a representation of humanbehavior, often depicts how people in a culture think and talk and behave. The objective of literature is toeducate, instruct, and amuse via tales depicting human life and activity through characters who, throughtheir words, actions, and reactions, express particular themes.